2011
DOI: 10.1111/j.1526-100x.2011.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing Germination of Species for Hydroseeding Degraded Mediterranean Areas

Abstract: The germination performance of native species and their suitability for a rapid erosion control are uncertain. Together with their relatively low commercial availability and high costs, these are still strong reasons preventing their common use in hydroseeding for restoration of Mediterranean degraded slopes, despite the increasing number of studies recommending it. In this study, 14 non-native (commercial) and native herb and woody species were tested. Their germination performance was evaluated under laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
(56 reference statements)
1
22
1
Order By: Relevance
“…In the present study, and independent of the storage conditions and harvesting methods, the germination rates for the seed mixtures in the first year can be considered high, compared, for instance, with the results of Heilinger and Florineth () and Oliveira et al . (). In the first 2 years, the germination capacity of the SS material was, in general, higher than that of the OST material.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, and independent of the storage conditions and harvesting methods, the germination rates for the seed mixtures in the first year can be considered high, compared, for instance, with the results of Heilinger and Florineth () and Oliveira et al . (). In the first 2 years, the germination capacity of the SS material was, in general, higher than that of the OST material.…”
Section: Discussioncontrasting
confidence: 99%
“…Young plants used in restoration activities were mostly of local or regional provenance, probably also for logistic reasons, but plant seeds were not, as is often the case in many restoration projects (Kiehl et al, 2010;Oliveira et al, 2012;Tischew et al, 2011). Although the use of generalist and easily commercially available 'seed recipes' of exogenous or unknown provenances is a common practice particularly in largescale restoration projects, it may lead to the loss of local diversity of adapted varieties and possibly alter ecosystem functions Rowe, 2010;Vander Mijnsbrugge et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, the previous mulches were not resistant under heavy rain, the slurry tended to be disintegrated and finally seeds germinated in low rate. Moreover, research in laboratory, greenhouse, and field conditions conducted by Oliveira et al (2012) indicated that the success of local seed germination in the field has a low frequency. In order to improve the mulch performance, the natural gum could then be replaced by degradable tackifier.…”
Section: Introductionmentioning
confidence: 99%